Sex differences in track and field elite youth - Atkinson, M. A., James, J. J., Quinn, M. E., Senefeld, J. W., Hunter, S. K. (Medicine & Science in Sports & Exercise, 2024)
Purpose To understand athletic performance before and after puberty, this study determined: 1) the age at which the sex difference increases among elite youth track and field athletes for running and jumping events; and 2) whether there is a sex difference in performance prior to ages associated with puberty among elite youth athletes.